ASSISTANCE OF HEALTH ADMINISTRATORS IN CARRYING OUT THEIR DUTIES AND FUNCTIONS AT ABDOEL WAHAB SJAHRANIE HOSPITAL (Jurnal Abdimas Administrasi Kesehatan, 2021)
The purpose of this community service is to find out the implementation of the main duties and functions of health administration and to find out the obstacles in the implementation of these main tasks and functions. This community service methodology uses health administration planning, patterns and strategies in carrying out its duties and functions so that it can run well. Based on the results of the assistance of health administrators in carrying out their duties and functions at the Abdoel Wahab Sjahranie hospital, it can be concluded that the presentation of percentages such as exposure in the form of powerpoints that are the most in community service is that participants understand carrying out their duties and functions, namely as many as 15 respondents (95%) and those who do not understand carrying out their duties and functions as many as 5 respondents (5%). For the assistance of health administrators in carrying out their duties and functions at the Abdoel Wahab Sjahranie hospital, it is very good in its implementation.
Keywords: Asistance of Health Administration